Analysis of the Level of Community Participation in the Management of the Village Owned Enterprise (BUM Desa) “Surya Sejahtera” - Rachel Nella Aprillia; Kalvin Edo Wahyudi (Universitas Muhammadiyah Gorontalo, 2025)
Village Owned Enterprises are one example of community participation in village development. BUM Desa Surya Sejahtera, as the oldest BUM Desa and the first to be categorized as advanced in Taman Subdistrict, has been present in the community. However, behind its success, several of its business units have experienced stagnation, presumably due to a lack of community participation in the management of BUM Desa. This study aims to analyze and describe the level of community participationin the management of the Village Owned Enterprise “Surya Sejahtera” in Kedungturi Village, Taman Sub district, Sidoarjo District. This study employs community participation levels, which consists of five levels: information, consultation, deciding together, acting together, and supporting. The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. Data analysis in this study involves data collection, data condensation, data display, and verification. The results of this study show that the level of community participation in the management of BUM Desa Surya Sejahtera is at the level of acting together, as reflected in community involvement in the form of cooperation in several business units and community responsibility. However, this participation is not yet optimal due to low commitment and inadequate coordination in the management of the BUM Desa. Therefore, a clear strategy is needed regarding the division of responsibilities among all parties and effective coordination, accompanied by empowerment programs that encourage motivation and formulate policies to encourage tangible support from the community.